Selenium-Binding Protein 1 (SBP1) autoantibodies in ovarian disorders and ovarian cancer. Issue 3 (March 2017) - Yu-Rice, Yi; Edassery, Seby L; Urban, Nicole; Hellstrom, Ingegerd; Hellstrom, Karl Erik; Deng, Youping; Li, Yan; Luborsky, Judith L
Abstract : Infertility is a risk factor for ovarian cancer (OvCa). The goal was to determine if antibodies to selenium-binding protein 1 (SBP1), an autoantibody we identified in patients with premature ovarian failure (POF), occurs in both infertility and OvCa patients, and thus could be associated with preneoplasia. Anti-SBP1 was measured by immunoassay against recombinant SBP1, in sera from OvCa ( n  = 41), infertility ( n  = 92) and control ( n  = 87) patients. Infertility causes were POF, unexplained, irregular ovulation or endometriosis. The percent of anti-SBP1-positive sera was higher in POF ( P  = 0.02), irregular ovulation ( P  = 0.001), unexplained causes ( P  = 0.02), late (III–IV)-stage OvCa ( P  = 0.02) but was not significant in endometriosis, benign ovarian tumors/cysts, early stage (I–II) OvCa or uterine cancer compared to healthy controls. Anti-SBP1 was significantly higher in women with serous ( P  = 0.04) but not non-serous ( P  = 0.33) OvCa compared to controls. Also, we determined if anti-SBP1 was associated with CA125 or anti-TP53, markers often studied in OvCa. Anti-TP53 and CA125 were measured by established immunoassays. The ability of anti-SBP1 alone to discriminate infertility or OvCa from controls or when combined with anti-TP53 and CA125, to identify OvCa was evaluated by comparing the area under the curve (AUC) in ROC analysis. Anti-SBP1 alone discriminated infertility (AUC = 0.7; P  = 0.001) or OvCa (AUC = 0.67; P  = 0.03) from controls. The sensitivity and specificity of OvCa identification was increased by combining CA125, anti-TP53 and anti-SBP1 (AUC = 0.96). Therefore, anti-SBP1 occurs in infertile women with POF, ovulatory disturbances or unexplained infertility and in serous OvCa. This suggests an autoimmune process is associated with the development of serous OvCa.